(-9)=b+(-13)

Simple and best practice solution for (-9)=b+(-13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-9)=b+(-13) equation:


Simplifying
(-9) = b + (-13)
-9 = b + (-13)
-9 = b + -13

Reorder the terms:
-9 = -13 + b

Solving
-9 = -13 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-9 + -1b = -13 + b + -1b

Combine like terms: b + -1b = 0
-9 + -1b = -13 + 0
-9 + -1b = -13

Add '9' to each side of the equation.
-9 + 9 + -1b = -13 + 9

Combine like terms: -9 + 9 = 0
0 + -1b = -13 + 9
-1b = -13 + 9

Combine like terms: -13 + 9 = -4
-1b = -4

Divide each side by '-1'.
b = 4

Simplifying
b = 4

See similar equations:

| 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) | | 10y-2x=50 | | 6x+12+2x+60=90 | | -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 |

Equations solver categories